Micro and nanodevices for thermoelectric converters - Carmo, João Paulo Pereira (2011)
The focus of this chapter is the presentation of micro and nanodevices for thermoelectric converters. Examples of applications for these converters are (1) in the conversion of electrical energy from temperature gradients and (2) in cooling devices. These converters are of solid-state type and use pairs of thermoelectric pand n-type materials, which were obtained by thin-films depositions. In this context, issues such the fabrication and characterization details of materials are discussed. The materials selected to serve as p- and n-type structures were the antimony telluride (Sb2Te3) and the bismuth telluride (Bi2Te3). The thin-films depositions of both Bi2Te3 and Sb2Te3 materials require a precise controlled process to achieve the highest possible thermoelectric figure-of-merit, ZT, and at the same time to achieve the desire composition. This goal is achieved with the co-evaporation of antimony (Sb)/bismuth(Bi) and telluride (Te) technique. It is also analyzed the influence of the parameters involved in the depositions (e.g., the temperature which the substrate is subjected, and the evaporation rates of Sb/Bi and Te), and their impacts in the final composition of Sb2Te3 and Bi2Te3 thin-films. Advanced issues and trends related to the fabrication of super-lattices for use in thermoelectric converters are also presented in this chapter.